Dramatic response and acquired resistance to savolitinib in advanced intrahepatic cholangiocarcinoma with MET amplification: a case report and literature review - Zhou, Kexun; Liu, Yingping; Zhu, Hong (Frontiers in Oncology, 2023)
Background Cholangiocarcinoma (CCA) is an aggressive disease with limited treatment options. Despite substantial efforts to explore better regimens, gemcitabine-based chemotherapy has been the standard first-line treatment for decades. With the growing field of precision medicine, biomarker-guided treatments are gaining popularity. MET alteration is a frequent occurrence in various cancer types, making it a promising target. Case presentation A 53-year-old man visited our hospital with a complaint of upper abdominal pain. Advanced CCA was diagnosed based on the biopsy of the metastatic lymph nodes and immunohistochemistry. Next-generation sequencing revealed MET amplification. As the patient was intolerant to traditional chemotherapy, savolitinib (a c-MET inhibitor) was administered. Partial response was achieved, and the treatment was well tolerated. After one year, the patient developed progressive disease, to which the emergence of epidermal growth factor receptor amplification may have contributed. Conclusion Our study verified the therapeutic value of a c-MET inhibitor in advanced CCA-harboring MET amplification and provides an alternative strategy for patients who are intolerant to chemotherapy.